PENGARUH INTELLECTUAL CAPITAL TERHADAP FIRM VALUE DENGAN CAPITAL STRUCTURE SEBAGAI VARIABEL MEDIASI - Yehezkiel Iwan Kurniawan, Hendro Lukman (Fakultas Ekonomi, Universitas Tarumanagara, 2020)
The purpose of this research is to obtain empirical evidence about the effects of Intellectual Capital on Firm Value using Capital Structure as mediating variabel. The research is conducted by taking 79 samples from manufacturing companies subsector food and beverage which announce their financial statements from 2014 to 2018. Statistical Package for the Social Sciences (SPSS) ver. 24 and smartPLS 3.0 are used to analyze data. The results show that Intellectual Capital have a significant influence on Firm Value. Besides, Capital Structure can mediating the effect of Intellectual Capital on Firm Value, although it reduces the influence of IC directly.